Remnant cholesterol, stronger than triglycerides, is associated with incident non-alcoholic fatty liver disease - Cheng, Yiping; Zhang, Qiang; Li, Haizhen; Zhou, Guangshuai; Shi, Ping; Zhang, Xu; Guan, Liying; Yan, Fang; Xu, Chao (Frontiers in Endocrinology, 2023)
Introduction Non-alcoholic fatty liver disease (NAFLD) is characterized by excess accumulation of triglycerides within the liver. However, whether the circulating levels of triglycerides and cholesterol transported in triglyceride-rich lipoproteins (remnant cholesterol, remnant-C) are related to the occurrence of NAFLD has not yet been studied. This study aims to assess the association of triglycerides and remnant-C with NAFLD in a Chinese cohort of middle aged and elderly individuals. Methods All subjects in the current study are from the 13,876 individuals who recruited in the Shandong cohort of the REACTION study. We included 6,634 participants who had more than one visit during the study period with an average follow-up time of 43.34 months. The association between lipid concentrations and incident NAFLD were evaluated by unadjusted and adjusted Cox proportional hazard models. The potential confounders were adjusted in the models including age, sex, hip circumference (HC), body mass index (BMI), systolic blood pressure, diastolic blood pressure, fasting plasma glucose (FPG), diabetes status and cardiovascular disease (CVD) status. Results In multivariable-adjusted Cox proportional hazard model analyses, triglycerides (hazard ratio[HR], 95% confidence interval [CI]:1.080,1.047-1.113;p<0.001), high-density lipoprotein cholesterol (HDL-C) (HR, 95% CI: 0.571,0.487-0.670; p<0.001), and remnant-C (HR, 95% CI: 1.143,1.052-1.242; p=0.002), but not total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C), were associated with incident NAFLD. Atherogenic dyslipidemia (triglycerides>1.69 mmol/L, HDL-C<1.03 mmol/L in men or<1.29 mmol/L in women) was also associated with NAFLD (HR, 95% CI: 1.343,1.177-1.533; p<0.001). Remnant-C levels were higher in females than in males and increased with increasing BMI and in participants with diabetes and CVD compared with those without diabetes or CVD. After adjusting for other factors in the Cox regression models, we found that serum levels of TG and remnant-C, but not TC or LDL-C, were associated with NAFLD outcomes in women group, non-cardiovascular disease status, non-diabetes status and middle BMI categories (24 to 28 kg/m2). Discussion In the middle aged and elderly subset of the Chinese population, especially those who were women, non-CVD status, non-diabetes status and middle BMI status (24 to 28 kg/m2), levels of triglycerides and remnant-C, but not TC or LDL-C, were associated with NAFLD outcomes independent of other risk factors.